Orientational dependence of the affinity of guanidinium ions to the water surface - Wernersson, Erik; Heyda, Jan; Vazdar, Mario; Lund, Mikael; Mason, Philip E; Jungwirth, Pavel (The journal of physical chemistry. B, 2011)
The behavior of guanidinium chloride at the surface of aqueous solutions is investigated using classical molecular dynamics (MD) simulations. It is found that the population of guanidinium ions oriented parallel to the interface is greater in the surface region than in bulk. The opposite is true for ions in other orientations. Overall, guanidinium chloride is depleted in the surface region, in agreement with the fact that the addition of guanidinium chloride increases the surface tension of water. The orientational dependence of the surface affinity of the guanidinium cation is related to its anisotropic hydration. To bring the ion to the surface in the parallel orientation does not require hydrogen bonds to be broken, in contrast to other orientations. The surface enrichment of parallel-oriented guanidinium indicates that its solvation is more favorable near the surface than in bulk solution for this orientation. The dependence of the bulk and surface properties of guanidinium on the force field parameters is also investigated. Despite significant quantitative differences between the force fields, the surface behavior is qualitatively robust. The implications for the orientations of the guanidinium groups of arginine side chains on protein surfaces are also outlined.
Keywords: Surface Tension; simulace molekulární dynamiky; vodíková vazba; Guanidine; guanidin; Ions; Water; Molecular Dynamics Simulation; Hydrogen Bonding; povrchové napětí; voda; ionty